PENGARUH MODEL INKUIRI TERBIMBING MATERI KOROSI TERHADAP KETERAMPILAN KERJA ILMIAH SISWA SMAN 6 PONTIANAK - Siti Aisyah; Hairida Hairida; Ira Lestari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe aims of this research were to determine difference in the students’ scientific work skills before and after implementing the guided inquiry model and determine the amount of effect the guided inquiry model of sientific work skill on corrosion material. The form of this research was pre-experimental design with one-group pretest-posttest design. Data collection tools used were scientific work skills test, observation sheets, and interview guildelines. Independent sample T test was used to analyze scientific work skills before and after the guided inquiry model was applied. The scientific work skills of students before and after guided inquiry learning were in the category of unskilled, less skilled, skilled and highly skilled. Independent sample T test result showed that the value of Asymp. Sig. (2-tailed) was 0,000, wich mean less than 0,05 (>0.05). Score of N-gain shows that value of 0,6, which mean amount of effect the guided inquiry model of sientific work skill on corrosion material was medium. In conclusion, there were differences in the students’ scientific work skills before and after the guided inquiry model was applied.Keywords: Guided Inquiry, Scientific Work Skills, Corrosion.